纯电动汽车的滑动能量回收方法、装置及纯电动汽车 (2018)
本发明提供了种纯电动汽车的滑动能量回收方法、装置及纯电动汽车，该方法包括：判断纯电动汽车是否进入滑动能量回收模式；当所述纯电动汽车进入所述滑动能量回收模式时，获取所述纯电动汽车的行驶工况信息；根据所述行驶工况信息确定所述滑动能量回收模式所需的目标扭矩；根据所述目标扭矩，控制所述纯电动汽车的电机进入发电状态，进行滑动能量回收。本发明的方案，考虑了不同行驶工况下驾驶员不同的回收扭矩需求，提高了驾驶员的驾驶感受。 The invention provides a sliding energy recycling method and device of a pure electric vehicle and the pure electric vehicle. The method comprises the steps of judging whether the pure electric vehicle enters a sliding energy recycling mode or not; when the pure electric vehicle enters the sliding energy recycling mode, obtaining driving condition information of the pure electric vehicle; according to the driving condition information, determining target torque needed by the sliding energy recycling mode; according to the target torque, controlling a motor of the pure electric vehicle to enter the power generation status, and performing sliding energy recycling. According to the scheme, different torque recycling requirements of drivers under different driving conditions are considered, and the driving feel